THE MADURESE PREFIXES IN ELEMENTARY SCHOOL TEXTBOOKS: A CORPUS-BASED STUDY - Hadiqotul Jannah; Fitriyatuz Zakiyah; Eka Susylowati (Department of Master of Linguistic, Universitas Airlangga, 2026)
Madurese language as a cultural heritage is now rarely used due to modernization, especially by the younger generation. This makes learning Madurese in elementary schools an important step for its preservation, one of which is by studying the language. This research aims to find out how often prefixes are used in class IV Madurese textbooks and analyze their grammatical functions. This research uses descriptive qualitative method. The data in this research is a corpus of Madurese text data taken from Madurese language textbook class IV. The data is processed using Antconc application to find the most frequently used prefixes in the data. The result shows that there are 686 prefixes with a-, ka'-, è-, ng-, ka-, and pa- as the most frequently used prefixes. These prefixes function to form verbs, adjectives, and adverbs. The results of this study show that textbooks play an important role in preserving the Madurese language while helping students learn the language better.